Optimalisasi Pemberdayaan UMKM Budidaya dan Pengolahan Jamur Tiram Dalam Menjaga Stabilitas Ekonomi Pasca Pandemi Covid-19 - Pribadi, Ulung; Aji, Juhari Sasmito; Hayati, Kemala (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Trihanggo village has the right temperature and humidity for the proliferation of microscopic spores to support fungal growth. So that it becomes a potential for mushroom cultivation in order to build innovative economic activities that form MSMEs as service partners. The marketing strategy contained in MSMEs has not been able to reach wider consumers in the midst of the upheaval of the Covid-19 outbreak that has shaken the economy, especially the micro economy, namely MSMEs. This is in the background with the partner's problem regarding the low literacy of managers in the intangible context of the use of information technology in the marketing sector. The absence of labeling and product packaging innovations on processed mushrooms creates a risk of product counterfeiting and damage. The solution to be achieved is to utilize information technology with a foundation of quality human resources who are capable and technologically literate. Management of business units by creating new business units according to village potential and asset analysis accompanied by community involvement. Application of information and communication technology to support the productivity of programs and activities covering the administration and marketing fields to support human resources in order to achieve technology literacy, labeling adjustments packaging according to safety standards. The implementation methods offered are 1) Socialization to strengthen literacy regarding the online marketing system. 2) Skills training with the implementation of labeling and information and communication technology operations. 3) Assistance packaging according to packaging standards. The results of the service have an impact on the partner group with comparison results after and before the implementation of the service, on strengthening the service capacity to get results (25%-70%), followed by the implementation of product labeling with results (30%-60%), and the impact of product packaging or renewal (30%-70%).